“Super hero stuff” e-commerce website / Wan Akmal Wan Mat - Wan Mat, Wan Akmal (2012)
Nowadays, the emergence of personalization application for online shopping in business industries is the new approach to help business gain most benefits for their companies. E-Commerce, with the Internet as its main platform has a very large market network. The research has contributed online shopping for the international superhero merchandise. “SuperHero Stuff” E-Commerce Website has brought the new ideas to find the international and limited “SuperHero Stuff” merchandise in Malaysia through online. “SuperHero Stuff” E-Commerce Website contributed the ideas in integrating the online shopping and hoping that all user around Malaysia can purchased the international superhero merchandise easily. The system provides facilities for customers to place orders, purchases and a recommend products based on customer needs electronically. The system developed in the Windows environment using Macromedia Dreamweaver 8 as the scripting language. While, MySQL and Wamp Server are used as the database management system. During the development process, the Waterfall Model is implemented where it acts as a methodology in developing the system. The development of such system is expected to be the driver for the growth of product sales and market.